Dynamic Instability of Pile-Supported Structures in Liquefiable Soils during Earthquakes - S. Adhikari; S. Bhattacharya (Shock and Vibration)
Piles are long slender columns installed deep into the ground to support heavy structures such as oil platforms, bridges, and tall buildings where the ground is not strong enough to support the structure on its own. In seismic prone zones, in the areas of soft soils (loose to medium dense soil which liquefies like a quick sand) piles are routinely used to support structures (buildings/ bridges). The pile and the building vibrate, and often collapse, in liquefiable soils during major earthquakes. In this paper an experimental and analytical approach is taken to characterize this vibration. The emphasis has been given to the dynamic instability of piled foundations in liquefied soil. The first natural frequency of a piled-structure vibrating in liquefiable soil is obtained from centrifuge tests. The experimental system is modelled using a fixed-free Euler-Bernoulli beam resting against an elastic support with axial load and tip mass with rotary inertia. Natural frequencies obtained from the analytical method are compared with experimental results. It was observed that the effective natural frequency of the system can reduce significantly during an earthquake.